2010
DOI: 10.1038/gene.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that glioma-associated oncogene homolog 1 is not a universal risk gene for inflammatory bowel disease in Caucasians

Abstract: The transcription factor glioma-associated oncogene homolog 1 (GLI1) has a central function in gastrointestinal tract development and homeostasis. A non-synonymous single-nucleotide polymorphism (SNP) (rs2228226; Q1100E) in GLI1, which impairs GLI1 function in vitro, has been proposed as a risk factor for inflammatory bowel disease (IBD). In this study, we assessed the cumulative evidence for association of GLI1 with IBD. New genotype data for rs2228226 from New Zealand (907 controls, 990 IBD patients) and Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The aim of this study was to replicate and expand on the findings of Noble et al. 1 by investigating the association of three SNPs of the VDR gene, rs11568820, rs2228570 and rs731236 , in a well‐phenotyped, Caucasian IBD cohort 4, 5 . All participants gave informed consent and ethical approval for the study was obtained.…”
Section: Minor Allele Frequency (Maf) and Odds Ratios (Or) Of The Vdmentioning
confidence: 89%
“…The aim of this study was to replicate and expand on the findings of Noble et al. 1 by investigating the association of three SNPs of the VDR gene, rs11568820, rs2228570 and rs731236 , in a well‐phenotyped, Caucasian IBD cohort 4, 5 . All participants gave informed consent and ethical approval for the study was obtained.…”
Section: Minor Allele Frequency (Maf) and Odds Ratios (Or) Of The Vdmentioning
confidence: 89%
“…Bentley and colleagues showed that the identified GLI1 SNP does not increase susceptibility to IBD across all the Caucasian populations, but it also does not exclude a contribution to UC onset in the populations studied by Lees et al . [162]. …”
Section: Hedgehogmentioning
confidence: 99%